Influência da incorporação dos polímeros de glicerol nas propriedades finais do pet reciclado pós-consumo (PET-PCR) - Seixas, Ana Amélia de Aragão (2022)
During the processing and reprocessing of poly(ethylene terephthalate) (PET) its molar mass is reduced. One way to minimize or stabilize this effect is to insert a substance capable of joining the ends of the chains to form a unique molecular structure, know as chain extenders. Glycerol-based polymers are polyfunctional and have hydroxyl and carboxylic groups in their chemical structure capable of acting as potential chain extenders. In the present work, we studied the influence of glycerol polymers: poly(glycerol citrate) (PGC), poly(glycerol succinate) (PGSu) and poly(glycerol citrateco- succinate) (PGCSu) as potential chain in the reactive mixture with post-consumer recycled PET (PET-PCR). Polymer blends of glycerol at a mass concentration of 2% (m/m) and recycled PET were processed in an internal mixer at 265°C for 6min and 60rpm. Then, they were characterized by viscosimetry, determination of carboxylic end groups (CEG) through the Pohl method, determination of the crosslinking degree as the percentage of insoluble gel, Fourier transform infrared spectroscopy (FTIR), thermogravimetry (TG) and calorimetry differential exploratory (DSC). During processing, it was observed that the incorporation of glycerol polymers increased the fluidity in the post-consumer PET resin, consequently decreasing its viscosity by 33% for PET-PCR/PGC, 24% for PET-PCR/PGSu, 44 % for PET-PCR/PGCSu and 17% for PET-PCR/Joncryl; the molar mass in the order of 42% for PET-PCR/PGC, 31% for PET-PCR/PGSu, 55% for PET-PCR/PGCSu and 23% for PET-PCR/Joncryl and increasing the number of terminal carboxylic groups. Although they did not show extensive chain crosslinking, the samples were fragile and brittle, thus making a mechanical test impossible. In the FTIR analysis, the occurrence of characteristic bands of carbonyl grouping (1715-1706cm-1) and ester bonds (1240-1100 cm-1) was observed, showing the efficiency of the mixture and polymerization in the stoichiometries studied. Thermogravimetry showed that the polyesters were thermally stable up to approximately 350°C and the sample that showed the fastest onset of thermal decomposition was the PET-PCR/PGCSu precisely due to the 55% reduction in molar mass. The DSC results showed a practically constant melting temperature and glass transition between the samples, a decrease of 8°C in the crystallization temperatures and an increase in the degree of crystallinity in relation to pure PET-PCR, which corroborates the results presented by the induced viscosity by the reduction in molar mass. These results indicated that at the concentration and processing conditions used, the potential additives to chain extenders had an opposite effect to the desired one, that is, they reduced the molar mass of recycled PET, but the same effectal so occurred with the commercial chain extender. However, the additive that showed the greatest potential for use was PGSu, which presented results similar to the commercial chain extender Joncryl.